Resistance of the respiratory system measured with forced oscillation technique (FOT) correlates with bronchial thermoplasty response - Goorsenberg, Annika W. M.; d’Hooghe, Julia N. S.; Slats, Annelies M.; van den Aardweg, Joost G.; Annema, Jouke T.; Bonta, Peter I. (Respiratory research, 2020)
Background Bronchial Thermoplasty (BT) is an endoscopic treatment for severe asthma using radiofrequency energy to target airway remodeling including smooth muscle. The correlation of pulmonary function tests and BT response are largely unknown. Forced Oscillation Technique (FOT) is an effort-independent technique to assess respiratory resistance (Rrs) by using pressure oscillations including small airways. Aim To investigate the effect of BT on pulmonary function, assessed by spirometry, bodyplethysmography and FOT and explore associations between pulmonary function parameters and BT treatment response. Methods Severe asthma patients recruited to the TASMA trial were analyzed in this observational cohort study. Spirometry, bodyplethysmography and FOT measurements were performed before and 6 months after BT. Asthma questionnaires (AQLQ/ACQ-6) were used to assess treatment response. Results Twenty-four patients were analyzed. AQLQ and ACQ improved significantly 6 months after BT (AQLQ 4.15 (±0.96) to 4.90 (±1.14) and ACQ 2.64 (±0.60) to 2.11 (±1.04), p = 0.004 and p = 0.02 respectively). Pulmonary function parameters remained stable. Improvement in FEV 1 correlated with AQLQ change ( r = 0.45 p = 0.03). Lower respiratory resistance (Rrs) at baseline (both 5 Hz and 19 Hz) significantly correlated to AQLQ improvement ( r = − 0.52 and r = − 0.53 respectively, p = 0.01 (both)). Borderline significant correlations with ACQ improvement were found ( r = 0.30 p = 0.16 for 5 Hz and r = 0.41 p = 0.05 for 19 Hz). Conclusion Pulmonary function remained stable after BT. Improvement in FEV 1 correlated with asthma questionnaires improvement including AQLQ. Lower FOT-measured respiratory resistance at baseline was associated with favorable BT response, which might reflect targeting of larger airways with BT. Trial registration ClinicalTrials.gov Identifier: NCT02225392 ; Registered 26 August 2014.